Immobilization of cellulases enzyme on Carbon Nanotubes (CNTs) for cellulosic compounds degradation - Al-Khatib, Ma An Fahmi Rashid; Alam, Md. Zahangir; Mohammed Abd, Rasha (2010)
The fast growing palm oil industry in Malaysia generates, amongst other wastes, Empty Fruit Bunch (EFB) which consists of cellulosic materials. It is one of the major sources of Greenhouse Gases (GHG). However, the bioconversion of cellulosic materials in EFB, a renewable biomass, to valuable products will be the solution to the disposal problem and hence minimize the pollution. The bioconversion of cellulosic materials is carried out by using cellulase enzyme, which itself was extracted from sludge, immobilized on functionalized carbon nanotubes (CNTs) in the presence of coupling reagent. The process parameters such as reaction temperature, reaction time, pH, and amount of enzyme, CNTs dosage and EDC were optimized by using design expert software. The morphology and the structure of CNTs were characterized by Field Emission Scanning Electron Microscopy (FSEM) and Fourier Transform Infrared Absorption Spectroscopic (FTIR). Firstly, carbon nanotubes were functionalized by acidic treatment. Then, the cellulase enzyme is immobilized on the functionalized (CNTs) in a solution of Nhydroxysuccinimide (NHS) and 1-ethyl-3-(3-dimethylamino propyl)-carbodiimide hydrochloride (EDC). The amount of enzyme attached on (CNTs) will be measured through UV spectrometer to determine the cellulases catalytic activity after immobilization and compare it with the free enzyme. Finally, the immobilized enzyme will be tested in the degradation of cellulosic material of empty fruit bunch (EFB) from palm oil mill effluent.